An ESD-oriented e-book based on siwalan of Tuban to enhance creative thinking skills - Shela Sonia; Y. Yuliani; I. Isnawati (University of Muhammadiyah Malang, 2024)
The 21st-century skills require education in Indonesia to train 4C skills (Communication, Collaboration, Critical thinking, and Creative thinking), which are fundamental parts of students facing the era of society 5.0, one of which is creative thinking skills. Teaching materials to support these skills still need to be improved. This research aims to produce e-book based on the local wisdom of Siwalan (Borassus flabellifer L.) from Tuban oriented to Education for Sustainable Development (ESD) to train students in grade X creative thinking skills on valid and practical biodiversity material. The validity of e-book was determined by three experts, namely two expert lecturers and one biology teacher. Readability test results measured the practicality of e-book. The results of the validity test obtained a score of 3.88, which is a very valid category, while the practicality test based on the fry graph was categorized as practical at level 10, suitable for the reading of grade X students. The results showed that the e-book based on Siwalan local wisdom is valid and practical for learning. Integrating contextual learning materials based on local wisdom can train 21st-century skills that foster students' concern for sustainable development.